Auto-correlation study on the surface profile finished by abrasive jet with grinding wheel as restraint. (1st October 2007) - Li, C.H.; Cai, G.Q.; Xiu, S.C.
Surface microcosmic topography finished by abrasive jet with grinding wheel as restraint was analysed. The mechanisms on peak removed and ripple homogenised of finished surface were also investigated. Experiments were performed with the plane grinder M7120 and the workpiece material Q235A, which was ground with the surface roughness values of Ra = 0.2 ? 0.4 µm. The machined surface morphology was studied using Scanning Electron Microscope (SEM) and the microscope and the microcosmic geometry parameters were measured with TALSURFY5 instrument. According to the experimental results, the surface topographical characteristics have also been evaluated with the correlation of random process about the surface by grinding and abrasive jet precision finishing. The results show that longitudinal geometry parameters' values of finishing machining surface were diminished compared with ground surface. Furthermore, the mean ripple peak distance was decreased and ripple and peak density were increased. The results indicate that surface quality machined with abrasive jet precision finishing was improved obviously.